Nutrition and Movement to Improve Quality of Life with Knee Osteoarthritis—The NUMOQUA Study - Sabine Chmelar; Elisabeth Höld; Gabriele Leitner; Stefan Nehrer; Oliver Neubauer; Karl-Heinz Wagner; Barbara Wondrasch (Proceedings)
Background and Objectives: Osteoarthritis (OA) has long been considered a degenerative disease of cartilage tissue resulting from bodily wear and tear. However, there is accumulating evidence that inflammation plays a key role in the pathogenesis of OA. In knee OA—the most common form of OA—exercise therapy as an effective component of early treatment mainly addresses functional deficits but not the inflammatory processes. In the course of the NUMOQUA project, an anti-inflammatory therapeutic diet named “Austrian OA Cuisine” was developed. It is based on the framework of the New Nordic Diet combined with the food-based dietary guidelines of Austria, the guidelines for OA, the Austrian food culture, and the principles of a sustainable diet. The present study examines the implementation of the “Austrian OA Cuisine” combined with the evidence-based exercise therapy GLA:D® (Good Life with osteoArthritis in Denmark) in patients with knee OA and the effects on quality of life, nutritional and inflammatory status, and oxidative stress parameters. Methods: A total of 60 participants aged 50 to 75 with knee OA will be included and randomly assigned either to the intervention group or the control group. All participants will undergo the GLA:D® program in the first six weeks. Additionally, the intervention group will receive nutritional group training and individual nutritional counseling on “Austrian OA Cuisine” over nine months. The control group will receive general information about a healthy lifestyle. Measurements at baseline and at four follow-up dates include nutritional, inflammatory, and oxidative stress parameters. Furthermore, anthropometric and behavioral parameters and clinical data will be assessed. Results: The recruitment of patients started in the autumn of 2022 and is expected to be completed by January 2024, followed by data collection inJanuary 2025. Discussion: The prevalence of OA is expected to increase in the future due to ongoing demographic changes and rising obesity rates. The expected results will provide important evidence on whether this interdisciplinary therapeutic approach could be a new, cost-effective, and sustainable strategy to address the disease process of OA without negative side effects.